Correlation of the refined Hurley classification for hidradenitis suppurativa with patient‐reported quality of life and objective disease severity assessment. (1st May 2019) - Rondags, A.; van Straalen, K.R.; van Hasselt, J.R.; Janse, I.C.; Ardon, C.B.; Vossen, A.R.J.V.; Prens, E.P.; van der Zee, H.H.; Horváth, B.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, debilitating, heterogeneous disease requiring different treatment approaches. Recently, we refined the classic Hurley classification into a seven‐stage classification in order to guide these treatment choices. This new classification subdivides Hurley stage I and II into three substages, namely mild (A), moderate (B) and severe (C) HS disease. Hurley stage III is not subcategorized and is always severe. Objectives: To investigate the correlation between the given severity grades of Hurley I and Hurley II in the refined Hurley classification, and the patient‐reported quality of life and physician‐assessed objective severity score. Materials and methods: In this cross‐sectional study, patients with HS participating in the observational cohorts of two Dutch tertiary referral centres were included before June 2017. The patient‐reported Dermatology Life Quality Index (DLQI) and physician‐assessed International HS Severity Score System (IHS4) scores were compared between the refined Hurley stages. Results: In total, 433 patients were analysed. DLQI and IHS4 scores increased within Hurley stage I and II from A through C. There was a significant positive correlation of DLQI and IHS4 with increasing refined Hurley substages [refined Hurley stage I (A, B and C) to DLQI: rs = 0·259, P < 0·001 and refined Hurley stage II (A, B and C) to DLQI: rs = 0·185, P = 0·010; refined Hurley stage I (A, B and C) to IHS4: rs = 0·603, P < 0·001 and refined Hurley stage II (A, B and C) to IHS4: rs = 0·532, P < 0·001]. Conclusions: The refined Hurley classification accurately correlates with HS severity assessed by both patients and clinicians. Therefore, the refined Hurley classification is a useful tool for the quick assessment of severity in HS.